Pengoptimalan Performa Database Pada Proses Transformasi Data Pada SQL Server: Optimizing Database Performance in the Data Transformation Process in SQL Server ​ - Setiya Budi, Desi; Syahrial, Hadi (Technomedia Journal, 2024)
A database itself is generally a collection of data stored systematically on a computer that can be processed or manipulated using software (application programs) to produce information. Defining a database includes specifications in the form of data types, data structures and also limitations on the data to be stored. One tool that is often used is SQL Server. Data processing itself takes a lot of time through various stages. During the data processing stage there is something called data transformation and data transfer. Which means data is sent from process A to Process B and changed. In this case, it is not information from data, but what is changed is not the content or value contained in it, but changes it into a form of information that can be easily received and read by readers of the information. In the transformation and transfer process, there were several obstacles experienced. What often happens is a matter of time. Time refers to the speed of the data process itself. Because if each process has a very slow speed it will take a lot of time, even though there are still many other processes that have to run. In this research, the techniques of  Indexing, Temporary Table and a combination of the two were used. In order to get results which one is faster to use. This research uses the True Experiment Design method with a repeated measurement design. In this research there will be several treatments, and carried out in more than one experiment.